Final answer:
To rewrite the quadratic equation y=x^2-10x-6 in vertex form, we can complete the square. The vertex form of a quadratic equation is y=a(x-h)^2+k, where (h,k) represents the vertex of the parabola. To complete the square, group the x-terms together and rewrite x^2-10x as (x^2-10x+25)-25 by adding and subtracting half the coefficient of the x-term squared.
Step-by-step explanation:
To rewrite the quadratic equation y=x^2-10x-6 in vertex form, we can complete the square. The vertex form of a quadratic equation is y=a(x-h)^2+k, where (h,k) represents the vertex of the parabola.
To complete the square, we need to group the x-terms together:
y=(x^2-10x)-6
We can rewrite x^2-10x as (x^2-10x+25)-25 by adding and subtracting the square of half the coefficient of the x-term (in this case, 25).
So, the equation becomes: y=(x^2-10x+25)-25-6
Simplifying further, we get: y=(x-5)^2-31